Terminal deoxynucleotidyl transferase is found in prothymocytes - Silverstone, AE (The Rockefeller University Press, 1976)
Terminal deoxynucleotidyl transferase is an enzyme which has the unique property of polymerizing polydeoxynucleotides onto a primer in the absence of a template (1,2). This enzyme is found both in the thymus and the bone marrow of birds, rodents, and humans (3-7). Whether the marrow cells that contain terminal transferase are related to thymocytes, or are on a separate pathway of differentiation, is not yet known (7,8). To determine the lineage of the murine bone marrow cells that have terminal transferase, we have investigated whether these cells have the antigen Thy-1 induced on the cells by treatment with thymopoietin (9). Thymopoietin is known to induce a set of characteristic T-cell markers including the Thy-1 alloantigen on the surface of a subpopulation of bone marrow cells committed to T-cell differentiation (prothymocytes) (10). Destruction of Thy- 1-positive cells after exposure to thymopoietin allows elimination of a substantial fraction of those bone marrow cells that can repopulate an irradiated thymus (11). We find that such an elimination after induction with the thymic polypeptide removes a substantial amount of terminal transferase from the bone marrow cell population, suggesting that at least one-half of the marrow cells bearing this enzyme are related to those found in the thymus.